Coping styles, social support and resilience as predictors of Post-Traumatic Stress Disorder - Lira, Larissa; Oudhof-van-Barneveld, Johannes; González Arratia López Fuentes, Norma Ivonne; Rodríguez Aguilar, Brenda (Horizonte Sanitario, 2024)
Objective: The objective was to determine whether the variables confrontation, social support and resilience predict the presence of post-traumatic stress disorder in adult patients in a public health institution. Materials and methods: An intentional non-probabilistic sample was employed, consisting of 100 adults residents of the State of Mexico. 91% of the participants are women between 18 and 60 years old (M = 40, S.D. = 11.51). A descriptive analysis was carried out, using central tendency and dispersion measures: the Kolmogorov-Smirnov normality test was subsequently performed, indicating the relevance of the Spearman Rho test to determine the correlation between the variables; finally, a stepwise multiple linear regression was used. Results: 53% of participants have PTSD. The regression analysis indicates that the total variance explained is 56%, being the reflexive cognitive analysis the factor that explains the most PTSD followed by evasive style, validation and positive reevaluation. Conclusions: The findings indicate that some styles of confrontation act as protective factors against PTSD, while others have a maladaptive function, so it is relevant to design strategies for the prevention and intervention of the disorder. Keywords: Post-traumatic Stress Disorder; Adults; Resilience; Social Support.